2008
DOI: 10.1002/cncr.23374
|View full text |Cite
|
Sign up to set email alerts
|

Lack of reliability of CA125 response criteria with anti‐VEGF molecularly targeted therapy

Abstract: BACKGROUNDCA125 is an accepted indicator of epithelial ovarian cancer (EOC) response and is used to monitor patients treated with cytotoxic chemotherapy. It is uncertain how CA125 is affected by molecularly targeted drugs. In this pilot study, the authors analyzed the utility of CA125 to predict disease behavior in patients who were receiving sorafenib, a Raf‐kinase/VEGFR2 inhibitor, and bevacizumab, an anti‐VEGF monoclonal antibody.METHODSFifteen of 42 patients had recurrent EOC. Patients received sorafenib 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…Limitations regarding the use of CA125 levels to follow disease during treatment with bevacizumab have also recently been reported. Our findings regarding the limitations of CA-125 are consistent with a prior study of 15 recurrent ovarian cancer patients treated with sorafenib and bevacizumab, in which the authors reported that CA-125 changes did not agree with objective imaging (67% concordance) in predicting disease behavior [28]. In retrospective analysis of 62 patients with persistent or recurrent ovarian or peritoneal cancer treated with bevacizumab (Gynecologic Oncology Group protocol 170-D), Randall and colleagues observed that CA-125 and RECIST-defined progression correlated in most cases (31% and 21%, respectively), but 12.9% of those with CA-125 defined progression remained progression-free according to RECIST criteria for at least 5.7 months [29].…”
Section: Discussionsupporting
confidence: 90%
“…Limitations regarding the use of CA125 levels to follow disease during treatment with bevacizumab have also recently been reported. Our findings regarding the limitations of CA-125 are consistent with a prior study of 15 recurrent ovarian cancer patients treated with sorafenib and bevacizumab, in which the authors reported that CA-125 changes did not agree with objective imaging (67% concordance) in predicting disease behavior [28]. In retrospective analysis of 62 patients with persistent or recurrent ovarian or peritoneal cancer treated with bevacizumab (Gynecologic Oncology Group protocol 170-D), Randall and colleagues observed that CA-125 and RECIST-defined progression correlated in most cases (31% and 21%, respectively), but 12.9% of those with CA-125 defined progression remained progression-free according to RECIST criteria for at least 5.7 months [29].…”
Section: Discussionsupporting
confidence: 90%
“…12 Azad et al hypothesized that molecularly targeted agents might modulate CA125 production and secretion, and examined its reliability. 13 Their study was the fi rst analysis of prospectively obtained CA125 samples with concurrent imaging in a trial of molecularly targeted agents using concomitant sorafenib (a Raf-kinase/VEGF receptor 2 inhibitor) and BV (an anti-VEGF monoclonal antibody) in epithelial ovarian cancer. The results showed that the RRs were similar between the CA125 criteria and RECIST imaging criteria; however, CA125 changes did not appear to correlate with earlier diagnosis of disease progression than that of RECIST imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was observed in a previously-published report of 15 patients treated with bevacizumab in combination with sorafenib, where CA-125-defined progression preceded RECIST-defined progression in 3 patients. 14 Our findings are hypothesis-generating and might have important implications for the design of future clinical trials and the management of patients on bevacizumab or other anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 81%